Using Dancesport as an Educational Resource for Improving Institutionalized Children’s Learning Strategies - Gabriela Tomescu; Monica-Iulia Stănescu; Mihaela Manos; Liliana Dina; Kamer-Ainur Aivaz (Children, 2023)
Introduction: Specialized studies mention that extracurricular activities (including dance) contribute to the stimulation of multiple intelligences, on whose development the educational process and academic success depend. The aims of the study were to investigate the benefits of dancesport for the development of institutionalized children’s learning strategies, and to examine gender-dependent differences in learning strategies, as well as to formulate possible recommendations regarding the practice of dance at the age of preadolescence, from the perspective of school success vectors. Methods: Through the School Motivation and Learning Strategies Inventory (SMALSI), we could observe the changes produced in children from the initial phase to the final assessment at the end of a dancesport program. The intervention took place over a period of six months with a frequency of two lessons per week, with each lesson lasting 60 min, and aimed to increase school motivation and performance, considering the learning strategies used by institutionalized children. Thirty institutionalized children, aged 11–12 years old, participated in the research, during which they did not engage in other extracurricular physical activities. The preadolescents were assessed using the School Motivation and Learning Strategies Inventory (SMALSI). This self-report rating scale measures nine areas associated with learning strategies, six of which focus on student strengths (study strategies, note-taking/listening skills, reading/comprehension strategies, writing/research skills, test-taking strategies, and time management/organization techniques), and three are aimed at student liabilities (low academic motivation, test anxiety, and concentration/attention difficulties). Results: The results show that the biggest improvements in the case of institutionalized children were recorded for study strategies, effectiveness of test-taking strategies, and concentration difficulties. Girls registered significantly better results than boys only in the case of study strategies and for writing/research skills (Mann–Whitney test was used). Discussion: The study demonstrates the benefits of dancesport practice for the development of institutionalized children’s learning strategies, creating a foundation for the improvement of their academic performance and school integration. Conclusions: At the end of the dance program, significant improvements in academic interest were observed due to the testing strategies used. Better results were also obtained for the scales of anxiety and difficulty concentrating during tests, where average scores decreased significantly.